Significance of Zinc Fertilizer on Nutrient Content and Uptake in Rice - T, Muthukumararaja.; Sriramachandrasekharan, M.V. (International Journal of Environment, Agriculture and Biotechnology, 2019)
A pot experiment was conducted during 2011 in a pot culture yard at Department of Soil Science and Agricultural Chemistry, Faculty of Agriculture, Annamalai University to studies on significance of zinc fertilizer on nutrient content and uptake in rice. The nutrient content and uptake of rice significantly improved on addition of graded dose of zinc in both Vertisol and Entisol. The result of experiment revealed that nutrient content and uptake ( Zn) increased with zinc levels at all stages of crop growth. Nutrient content decreased while nutrient uptake increased with advancement of rice crop. The zinc content and uptake was highest at 7.5 mg Zn kg-1.However the response of nutrient content and uptake in rice crop was higher in Entisol than Vertisol.